The Silent Struggle: Husserl’s Descriptive Phenomenological Approach to Mental Health Stigma and Coping Mechanism among House Job Doctors and Internee Nurses in Peshawar, Pakistan” (Journal of Medical & Health Sciences Review, 2025)
Background:House officers and internee nurses face heavy workload, stigma, and stress during transition from academics to clinical practice, influencing their mental health. Objective: To investigate mental health stigma and coping strategies among house job doctors and internee nurses, assessing institutional support and providing recommendations for improved mental health resources and stigma reduction.Material and Methods: A qualitative phenomenological design was used. One-on-one semi-structured interviews were conducted using purposive sampling technique with 15 house officers and 15 internee nurses, analyzed using thematic analysis. Bracketing, textual, and structural descriptions ensured rigor, with confidentiality and ethical approval taken form Peshawar Medical college. Results: Three main themes and one emerging theme were identified: transition from theory to practice, coping mechanisms, institutional role, and appreciation of nursing support. Participants reported stress from patient deaths, stigma from attendants, and mismatch between theoretical training and clinical realities. Coping included seeking guidance from seniors, teamwork of doctors with nurses, and self-regulation through patience and faith. Institutional gaps, including weak disciplinary policies and absence of counseling, intensified challenges. Supportive seniors and competent nurses were protective factors, reducing stress and fostering resilience among house officers. Conclusion:House officersand internee nurses experience both vulnerability and resilience in their transition phase. Strengthening institutional policies, fostering teamwork, and providing structured mental health support are vital to protect their well-being and professional growth.